Impact of Bank Profitability on Default Risk: Empirical Evidence from Pakistan: Risk Management - Khalid, Waqar; Khan, Saifullah; Zahra, Anum; Shah, Naveed Hussain (Journal of Quantitative Methods, 2021)
This empirical study investigates the effect of the bank-specific determinants of bank profitability on the default risk of the banks listed on the Stock Exchange of Pakistan. For this purpose, the study considers balanced panel data covering the period 2009-2018 for the 20 selected commercial banks of Pakistan, and the probability of default is used to measure the default risk of these banks. The bank profitability is measured using bank-specific determinants such as the net interest margin, non-interest income to total assets, return on assets, return on equity, and spread ratios. The empirical findings of the fixed effects model reported that net interest margin, non-interest income, and spread ratio are the significant determinants of default risk. The findings highlight that the bank profitability determinants can act as early warning signs of a bank’s deteriorating stability level. The study recommended that the central bank of Pakistan should guide the commercial banks to disclose the probability of default values in their financial reports. The study also suggested that the risk management department of a bank should consider these bank-specific determinants of profitability to manage default risk.